2012
DOI: 10.1111/j.1365-2885.2012.01411.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and the effect of application site on a novel, long‐acting transdermal fentanyl solution in healthy laboratory Beagles

Abstract: the effect of application site on a novel, long-acting transdermal fentanyl solution in healthy laboratory Beagles. J. vet. Pharmacol. Therap. 35 (Suppl. 2), 27-33. Application of transdermal drugs to different anatomical sites can result in different absorption characteristics. The pharmacokinetics (PKs) and bioequivalence of a single 2.6 mg ⁄ kg (50 lL ⁄ kg) dose of a novel, long-acting transdermal fentanyl solution were determined when applied topically to the ventral abdominal or dorsal interscapular skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 19 publications
5
35
0
Order By: Relevance
“…9 A single application applied to the interscapular skin of beagles resulted in plasma concentrations consistent with analgesia 4 hours after administration and lasting for 96 hours. 10 When compared with intermittent injection of other opioids (buprenorphine and oxymorphone), this formulation was found to be effective and safe. 11,12 It should also be noted that the opioid antagonist naloxone was able to reverse the effects of overdose when administered at hourly intervals.…”
Section: How Do I Create An Analgesic Plan?mentioning
confidence: 97%
“…9 A single application applied to the interscapular skin of beagles resulted in plasma concentrations consistent with analgesia 4 hours after administration and lasting for 96 hours. 10 When compared with intermittent injection of other opioids (buprenorphine and oxymorphone), this formulation was found to be effective and safe. 11,12 It should also be noted that the opioid antagonist naloxone was able to reverse the effects of overdose when administered at hourly intervals.…”
Section: How Do I Create An Analgesic Plan?mentioning
confidence: 97%
“…The minimal fluctuations in the pharmacokinetic profile exhibited by TFS have been demonstrated in several laboratory dog studies (Freise et al. , 2012b,c).…”
Section: Introductionmentioning
confidence: 95%
“…Following dosing, the systemic concentrations of drug remain relatively constant because of a rapid fentanyl deposition into the stratum corneum, from where fentanyl is then steadily delivered into plasma absent of peaks and troughs. These laboratory studies demonstrated that when applied to the dorsal scapular area, mean plasma fentanyl concentrations remained above 0.5 ng/mL through 96 h postdose administration (Freise et al. , 2012b), a concentration that resides in the analgesic range (Kyles et al.…”
Section: Introductionmentioning
confidence: 99%
“…An issue of the Journal of Veterinary Pharmacology and Therapeutics was published in June 2012 with studies on the safety, efficacy, and PK‐PD of Recuvyra ® in dogs (Freise et al ., ,b,c,d; KuKanich & Clark, ; Linton et al ., ; Riviere, ; Savides et al ., ). The drug is applied to the skin 2–4 h before surgery and may provide analgesia after single application for up to 4 days postadministration (KuKanich & Clark, ).…”
Section: Current Knowledge Misconceptions and Controversies: The Romentioning
confidence: 99%